Optimizing The Use of Instagram as a Promotional Medium from The Perspective of Islamic Ethics in The Mega Rezky Health Vocational School Library, Makassar - Ramadayanti, Ramadayanti (Al-Hikmah Journal for Religious Studies, 2025)
This study discusses optimizing Instagram as a promotional medium for the Makassar Health Vocational School Library. The research focuses on two main aspects: the type of content promoted and the strategies employed for promotional activities. The study aims to identify effective content and optimal strategies to enhance the visibility of library services on Instagram. The study employed a qualitative research approach involving observation, interviews, and documentation techniques. Five informants were selected through purposive sampling: two librarians, a social media manager, a teacher, and two active library users. Data analysis was conducted according to the Miles and Huberman model through reduction, presentation, and conclusion drawing. The research findings show that promoted content includes service information, the latest collections, literacy education, and documentation of student literacy activities. Effective strategies include using attractive visuals, maintaining a consistent upload schedule, and actively interacting with followers. This study confirms that optimizing content and promotional strategies on Instagram increases student engagement and awareness of library services. Additionally, applying Islamic communication ethics based on tabligh, amanah, and ihsan ensures that promotional messages are educational, honest, and beneficial to users.